2005
DOI: 10.1037/1053-0797.15.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in the Diary and REM Dreams of Young and Late Adulthood Women and Their Relation to Life Satisfaction.

Abstract: Expanding on studies of the incidence and valence of emotions in dreams and their relationship with waking life satisfaction, home and rapid eye movement (REM) sleep dreams were collected from 30 late adulthood and 28 young women who had filled out a life satisfaction scale. Four positive and 4 negative dream emotions were self-rated. Both groups reported more emotions, with greater intensity, in home dreams than in REM dreams, particularly the older group. Regardless of age, intensity of negative emotions was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
2
29
1
1
Order By: Relevance
“…Whilst there is an array of literature concerning negative emotions in dreams, the evidence from dream science suggests that experiences typically incorporated into dreams are more emotionally intense than those that are not incorporated, but are not specifically negatively valenced ( Schredl and Doll, 1998 ; Schredl, 2006 ; Horton et al, 2011 ; Malinowski and Horton, 2014a ). Some studies indicate that there is a ‘negativity bias’ in dreams – the tendency for dreams to be more negatively than positively valenced ( Hall and Van de Castle, 1966 ; Snyder, 1970 ; Nielsen et al, 1991 ; Domhoff, 1996 ) – but others have found a balance between positive and negative emotions in dreams ( Strauch and Meier, 1996 ; Kahn and Hobson, 2002 ; St-Onge et al, 2005 ). Furthermore, studies that have compared external ratings of emotions to participants’ self-ratings of emotions find that external raters overestimate negative emotions in dreams compared to what the dreamers themselves perceive in the dreams ( Schredl and Doll, 1998 ; Sikka et al, 2014 ), indicating that it is the method that produces the negativity bias.…”
Section: Arguments For and Against Emotion-processing Theoriesmentioning
confidence: 99%
“…Whilst there is an array of literature concerning negative emotions in dreams, the evidence from dream science suggests that experiences typically incorporated into dreams are more emotionally intense than those that are not incorporated, but are not specifically negatively valenced ( Schredl and Doll, 1998 ; Schredl, 2006 ; Horton et al, 2011 ; Malinowski and Horton, 2014a ). Some studies indicate that there is a ‘negativity bias’ in dreams – the tendency for dreams to be more negatively than positively valenced ( Hall and Van de Castle, 1966 ; Snyder, 1970 ; Nielsen et al, 1991 ; Domhoff, 1996 ) – but others have found a balance between positive and negative emotions in dreams ( Strauch and Meier, 1996 ; Kahn and Hobson, 2002 ; St-Onge et al, 2005 ). Furthermore, studies that have compared external ratings of emotions to participants’ self-ratings of emotions find that external raters overestimate negative emotions in dreams compared to what the dreamers themselves perceive in the dreams ( Schredl and Doll, 1998 ; Sikka et al, 2014 ), indicating that it is the method that produces the negativity bias.…”
Section: Arguments For and Against Emotion-processing Theoriesmentioning
confidence: 99%
“…As evidenced in Table 1, when dream reports are obtained using constant sampling (morning awakenings in both settings) and reporting (either written or oral in both settings) conditions, no differences between laboratory and home dream reports are found, at least when rated by external judges (Foulkes, 1979, study 3;Weisz and Foulkes, 1970). However, when non-constant sampling [home morning awakenings versus laboratory serial rapid eye movement (REM) awakenings] and reporting (written home dream reports versus verbal laboratory dream reports) conditions are used, home dream reports contain more emotions, especially negative emotions (Foulkes, 1979, study 4;Okuma et al, 1975;St-Onge et al, 2005). These differences may arise because, at home, dream reports derive from either REM or non-REM (NREM) sleep, whereas in the laboratory they derive from REM sleep.…”
Section: Introductionmentioning
confidence: 99%
“…This design has strong advantages compared to artificial sleep laboratory research. Firstly, participants are likely to dream about their current laboratory environment, which is no issue when sleeping at home, and laboratory dreams are usually less emotional than home dreams (Baekeland, 1969;Hobson & Stickgold, 1994;St-Onge, Lortie-Lussier, Mercier, Grenier, & De Koninck, 2005;Whitman, Pierce, Maas, & Baldridge, 1962). Furthermore, there is evidence that nightmares at home are more severe than nightmares in the lab (Fisher et al, 1970;Hartmann, 1984).…”
mentioning
confidence: 99%